2012
DOI: 10.2516/ogst/2011117
|View full text |Cite
|
Sign up to set email alerts
|

Technical Assessment of Isothermal and Non-Isothermal Modelings of Natural Gas Pipeline Operational Conditions

Abstract: Résumé -Évaluation technique de modélisations isothermes et non isothermes de conditions opérationnelles de conduites de gaz naturel -Une modélisation d'équipement au sein d'un gazoduc a été réalisée en dérivant une nouvelle forme d'ensemble d'équations de conservation pour un écoulement compressible. Une section du troisième réseau de distribution de gaz iranien (Nourabad-PatavehDorahan, N-P-D) a été ensuite étudiée selon des approches de modélisation isotherme (IT) et non isotherme (NIT) en prenant en compte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…The continuity equation and momentum equation are also called hydraulic equations, and the energy equation is also called the thermodynamic equation. These equations can be written in a general form (Sanaye and Mahmoudimehr, 2012;Zheng et al, 2012;Duan et al, 2013;Wang et al, 2015Wang et al, , 2018, as shown in Equation 1, and the parameters of the general form are given in Table 1.…”
Section: Governing Equationsmentioning
confidence: 99%
“…The continuity equation and momentum equation are also called hydraulic equations, and the energy equation is also called the thermodynamic equation. These equations can be written in a general form (Sanaye and Mahmoudimehr, 2012;Zheng et al, 2012;Duan et al, 2013;Wang et al, 2015Wang et al, , 2018, as shown in Equation 1, and the parameters of the general form are given in Table 1.…”
Section: Governing Equationsmentioning
confidence: 99%
“…The scale of natural gas pipeline networks is becoming increasingly larger and the topological structure is becoming increasingly more complex [4]. Prediction of the flow parameters in a natural gas pipeline network is important to managers who create the operating schedule and forecast potential risk [5,6]. Hydraulic simulation is the most common way to analyze the flow in a gas pipeline network [7,8].…”
Section: Introductionmentioning
confidence: 99%